2012
DOI: 10.1093/ehjci/jes057
|View full text |Cite
|
Sign up to set email alerts
|

Safety of echocardiographic contrast in hospitalized patients with pulmonary hypertension: a multi-center study

Abstract: The use of the EC agent Definity is safe in hospitalized patients with PHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…studied over 18 000 patients that underwent SE demonstrated endocardial border visualization with contrast in patients with suboptimal images resulted in comparable sensitivity (81% vs. 73%, P = NS) and diagnostic accuracy (82% vs. 77%, P = NS) for wall‐motion analysis compared with patients with optimal image quality . Other studies have also demonstrated the overall safety and low adverse event rate attributable to contrast use in echocardiography, even in a population with a high prevalence of pulmonary disease …”
Section: Discussionmentioning
confidence: 91%
“…studied over 18 000 patients that underwent SE demonstrated endocardial border visualization with contrast in patients with suboptimal images resulted in comparable sensitivity (81% vs. 73%, P = NS) and diagnostic accuracy (82% vs. 77%, P = NS) for wall‐motion analysis compared with patients with optimal image quality . Other studies have also demonstrated the overall safety and low adverse event rate attributable to contrast use in echocardiography, even in a population with a high prevalence of pulmonary disease …”
Section: Discussionmentioning
confidence: 91%
“…In our cohort patients, there was one minor adverse reaction, which resolved completely when the contrast administration was ceased. This equates to an adverse event rate of 4% which is significantly higher than most large case series . Echocardiographic contrast agents are safe in a broad range of pathologies and among heterogeneous patient populations .…”
Section: Discussionmentioning
confidence: 87%
“…In 2012, Wever-Pinzon et al . (40) published a retrospective series on 1513 consecutive inpatients with documented pulmonary hypertension who had received UCAs. These patients were followed for 24 h post-UCA administration for SAEs, including respiratory decompensation, hypotension, arrhythmias, syncope, convulsions, anaphylactic reactions, or death.…”
Section: Update On Uca Safety and Efficacy Data: March 2012 To Presentmentioning
confidence: 99%